THE ASSOCIATIVE EXPERIMENT IN LANGUAGE TEACHING - Gayubova Komila Anvarovna,, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. The article describes the issues of studying the features of mnemic activity with the ultimate goal of forming mnemic skills. This can be interpreted as a similarity between the action of associative reproduction of words and the work of memory  to  actualize  verbal  material,  which  inevitably  enters  into  any  language learning.